Clinical observation of different dosages of dexmedetomidine combined with a target-controlled infusion of propofol in hysteroscopic submucosal myomectomy - Li, Haibing; Zhao, Qingsong; Yu, Yibing; Li, Wei (Frontiers in Surgery, 2023)
Objective: This study aimed to explore the clinical effects of different dosages of dexmedetomidine (Dex) combined with a target-controlled infusion of propofol in hysteroscopic submucosal myomectomy. Methods: Ninety patients who underwent hysteroscopic submucosal myomectomy between September 2021 and March 2022 were enrolled and randomly divided into three groups, with 30 patients in each group. Patients in Groups A, B, and C received injections of 0.25, 0.5, or 0.75 μg/kg of Dex, respectively, by intravenous pump over 10 minutes. After this time, a maintenance dosage of 0.5 μg/kg/h was administered by intravenous infusion until the end of the surgery. Anesthesia was induced using 1.5 mg/kg of propofol and 0.3 μg/kg of sufentanil that were introduced through a laryngeal mask. The plasma concentration of propofol was maintained at 3 μg/ml by target-controlled infusion until the end of the surgery. The mean arterial pressure (MAP), heart rate (HR), and electroencephalographic bispectral index (BIS) were observed when the patient entered the operating room (T0), after catheter indwelling for anesthesia (T1), at the time of cervical dilation (T2), at the time of hysteroscopic surgery (T3), and at the end of the surgery (T4) in all three groups. Results: The intraoperative reductions of MAP and HR in patients were significant in Group C when compared with those in Groups A and B (P < 0.05), and BIS was significantly lower in Group C at T2 and T3 when compared with the baseline measurement at T0 (P < 0.05). The dosage of propofol was significantly higher for Group A than for Groups B and C (P < 0.05). The anesthesia awakening time and orientation recovery time were significantly longer for patients in Group C when compared with patients in Groups A and B (P < 0.05). Within 5–30 minutes after awakening, the VAS scores in Groups B and C were significantly lower than those for Group A (P < 0.05). Conclusion: The continuous pumping of 0.5 μg/kg of Dex combined with a target-controlled infusion of propofol in hysteroscopic submucosal myomectomy resulted in positive anesthetic and analgesia effects and fewer adverse reactions. It therefore has high clinical significance.